Effect of crack opening velocity and adhesive layer thickness on the fracture behaviour of hyperelastic adhesive joints subjected to mode I loading. (June 2018) - Schmandt, Christopher; Marzi, Stephan
Abstract: Wide usage of rubber-like adhesive joints requires knowledge about their fracture behaviour to predict the failure of such connections. The focus of this work is on the dependency of mode I failure on crack opening velocity and adhesive layer thickness concerning hyperelastic adhesive joints. Double cantilever beam specimens were manufactured with different adhesive layer thicknesses and tested at various cross head velocities. Using an analytical approach to calculate the J-integral directly from the measured data, traction-separation laws for cohesive zone modelling were extracted. Characteristic material parameters to define the shape of the cohesive law were chosen as the initial stiffness, the cohesive strength and the fracture energy. Analytical functions for cohesive strength and fracture energy were developed that can be used to define traction-separation laws depending on crack opening velocity and adhesive layer thickness.